2010
DOI: 10.17221/2984-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inhalation salbutamol administration on systemic and pulmonary hemodynamic, pulmonary mechanics and oxygen balance during general anaesthesia in the horse

Abstract: ABSTRACT:This research aimed to determine the effect of aerosolized salbutamol administration on systemic and pulmonary hemodynamic, pulmonary mechanics and oxygen balance in healthy horses during general anaesthesia. Six healthy Thoroughbreds (body weight range 471-587 kg) underwent two general anaesthesias in dorsal recumbency with and without aerosolized salbutamol administration in randomized order with a one month washout period. The anaesthesia was induced by 1.1 mg/kg of xylazine, 0.02 mg/kg of diazepam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This technique has been described by Robertson and Bailey [ 1 ] in clinical horses lying in dorsal recumbency and utilized by Patschova et al . [ 11 ] in experimental horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been described by Robertson and Bailey [ 1 ] in clinical horses lying in dorsal recumbency and utilized by Patschova et al . [ 11 ] in experimental horses.…”
Section: Discussionmentioning
confidence: 99%
“…However, no tachycardia was observed in horses following salbutamol administration in clinical settings [ 1 ]. In experimental healthy horses in dorsal recumbency, a positive chronotropic effect without clinical relevance was temporarily recorded [ 11 ]. This case series reports the occurrence of clinically relevant cardiovascular effects i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The horses were mechanically ventilated, and mean P was maintained above 70 mmHg. In a subsequent laboratory study, aerosolised albuterol (salbutamol, 2 μg/kg bwt) significantly increased cardiac output and DO 2 without changing CPS . The authors concluded that improvements in oxygen delivery resulted primarily from improved haemodynamics, indicating significant systemic absorption of the drug .…”
Section: Investigated Methods For Offsetting or Correcting Hypoxaemiamentioning
confidence: 97%
“…If hypoxaemia exists and the horse is normotensive (mean P>60 mmHg), minute ventilation should be normalised with controlled ventilation to produce a PaCO 2 of 5.3–6.7 kPa (40–50 mmHg). An additional intervention with little risk of significant side effects is the delivery of albuterol via the airway . A dose of 2 μg/kg bwt can be delivered via the endotracheal tube by interrupting the respiratory cycle, disconnecting the endotracheal tube from the anaesthetic machine, delivering the drug, reconnecting and delivering a V T .…”
Section: Analysis Of the Literature In Devising A Clinical Approach Tmentioning
confidence: 99%
“…This is a much lower driving pressure for the blood flow than the systemic circulation, where the arterial-venous pressure gradient is approximately 90 mmHg in humans. Table 1 summarizes the pulmonary hemodynamic parameters for other species from different studies (Barer and Nusser, 1957a;Drougas et al, 1996;Holm et al, 1998;Morris et al, 2000;Grant and Canty, 1989;Baxter et al, 1952;Duke and Stedeford, 1960;Chen et al, 2005;Yuan et al, 2011;Liu et al, 2005;Emery et al, 2001;Fesler et al, 2006;Chick et al, 1988;Franceschi et al, 2013;Chaliki et al, 2002;Romand et al, 1994;Takeda et al, 1987;Johnson et al, 1992;Ravikumar et al, 2011;Reddy et al, 1995;Polglase et al, 2006;Newman et al, 1993;Nachar et al, 2001;Krebs et al, 2007;Hinder et al, 1998;Pennington et al, 1992;Patschova et al, 2010;Stickland et al, 2007;Li et al, 2013;Goetz et al, 1999;Tournoux et al, 2011;Ortiz et al, 2002;Ullrich et al, 1999). Although the blood flow through the pulmonary circulation is essentially the same as the blood flow through the systemic circulation, the pulmonary vascular resistance is 10-to 15-fold lower than the systemic vascular resistance.…”
Section: Pulmonary Hemodynamicsmentioning
confidence: 99%